2010
DOI: 10.1037/a0020066
|View full text |Cite
|
Sign up to set email alerts
|

Children's early approaches to learning and academic trajectories through fifth grade.

Abstract: Children's early approaches to learning (ATL) enhance their adaptation to the demands they experience with the start of formal schooling. The current study uses individual growth modeling to investigate whether children's early ATL, which includes persistence, emotion regulation, and attentiveness, explain individual differences in their academic trajectories during elementary school. Using data from the Early Childhood Longitudinal Study - Kindergarten Cohort (ECLS-K), the present investigation examined the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
226
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(242 citation statements)
references
References 99 publications
13
226
2
1
Order By: Relevance
“…Specifically, this construct also tapped children's eagerness to learn, creativity, level of interest, and their emotion regulation particularly during interactions with peers (Li-Grining, et al, 2010). Based on LiGrining and colleagues' study, however, it seems possible that behavioral regulation may be more beneficial for boys' early literacy and girls' math school readiness skills in the United States.…”
Section: Gender Differences By Culture In the Relation Between Behavimentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, this construct also tapped children's eagerness to learn, creativity, level of interest, and their emotion regulation particularly during interactions with peers (Li-Grining, et al, 2010). Based on LiGrining and colleagues' study, however, it seems possible that behavioral regulation may be more beneficial for boys' early literacy and girls' math school readiness skills in the United States.…”
Section: Gender Differences By Culture In the Relation Between Behavimentioning
confidence: 88%
“…Previous research has found moderate correlations between direct assessments of individual behavioral regulation and teacher-ratings of classroom behavioral regulation of about r = .30, suggesting a degree of shared variance . Further, an examination of the items that teachers rate to assess classroom behavioral regulation suggests that in addition to tapping individual behavioral regulation, they may also reflect a broader construct, akin to "approaches to learning" and "learningrelated skills," including skills such as independence (Li-Grining, Votruba-Drzal, Maldonado-Carreno, & Haas, 2010). The unshared variance may reflect these differences, as well as differences in measurement sources (direct assessment versus teacher rating).…”
mentioning
confidence: 99%
“…However, most previous research examining these relationships has been conducted in adolescent samples (Baeten et al, 2010;Pennebaker, Gosling, & Ferrell, 2013;Sengodan & Zanaton, 2012). This is even more evident in the case of approaches to learning, where the very few studies that have been conducted in younger samples have commonly described these components as an indeterminate set of predispositions such as persistence, emotion regulation, or attentiveness, rather than emphasize the strategic nature of this construct (Bodovski & Youn, 2011;Li-Grining, Votruba-Drzal, Maldonado-Carreño, & Haas, 2010;Malmberg, Järvernoja, & Järvelä, 2013). Thus, further research is needed with younger students that extends this line of research.…”
Section: Conclusion From the Previous Researchmentioning
confidence: 99%
“…Approaches to learning includes being open to and curious about tasks and challenges, being persistent, flexible, imaginative, and attentive. Research has found that children's early approaches to learning enhance their ability to adapt to the demands they experience with the start of formal schooling (Li-Grining et al, 2010) such as completing work independently, adhering to strict time schedules, and acquiring basic skills. Language development is the fourth dimension of school readiness.…”
Section: School Readinessmentioning
confidence: 99%
“…In another area of research on school readiness, researchers have investigated the relationship between dimensions of readiness and later school achievement (Classens, Duncan, & Engel, 2009;Hair, Halle, Terry-Humen, Lavelle, & Calkins, 2006;Li-Grining, Votruba-Drzal, Maldonado-Carreño, & Haas, 2010;Romano et al, 2010). In these studies, children who enter kindergarten with a particular set of academic and social skills are more likely to be academically and economically successful in the future as compared to children who lack these attributes.…”
Section: Introductionmentioning
confidence: 99%